2019
DOI: 10.1111/1748-8583.12244
|View full text |Cite
|
Sign up to set email alerts
|

Contextual embeddedness of careers: female “nonsurvivors” and their gendered relational context

Abstract: Our aim is to contribute to a better understanding of the contextual embeddedness of women's careers. To do this, we leverage feminist relational theory (a) to understand the relational context of women's careers in Lebanon, with a particular focus on working‐self and career investments, and (b) to trace the gendered power dynamics of career investments in the relational context of work. Through examining the narratives of 24 Lebanese female “nonsurvivors” (i.e., used to work but are not currently engaged in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…A postconflict environment plagued by a slowing economy, host of millions of refugees, severe and repeated stalling of government, the 2020 devastating Beirut Explosion, and the surrounding instability of war on its southern and northern borders with the Syrian and the Israeli-Palestinian conflicts. This harsh context leads to high unemployment, and stunted career paths particularly among Lebanese women (Afiouni, Karam, & Makarem, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A postconflict environment plagued by a slowing economy, host of millions of refugees, severe and repeated stalling of government, the 2020 devastating Beirut Explosion, and the surrounding instability of war on its southern and northern borders with the Syrian and the Israeli-Palestinian conflicts. This harsh context leads to high unemployment, and stunted career paths particularly among Lebanese women (Afiouni, Karam, & Makarem, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Karam and Afiouni (2014) note that the barriers to workforce entry should be a key focus on women empowerment initiatives, in order to combat what they refer to as the bursting pipeline “where more and more Arab women are prepared with the necessary knowledge and skills, but are unable to secure employment” (Karam & Afiouni, 2014, p. 27). Despite these constraints, however, there is growing evidence of the possibility for successful career trajectories for Lebanese women (Afiouni et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Frehill et al (2008) found that 17% of women engineers in the USA opted out due to a lack of flexible work schedules and work–life balance, 19% of women left engineering due to lack of advancement opportunities, and negative work climate caused 15% of women to leave engineering. Afiouni et al (2020) found that women's career decisions in Lebanon are influenced by gender and power dynamics underlying social and relational interactions; gendered power dynamics shift women's connection with their working self to other selves, such as parental and spousal selves.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…At Middle Eastern Culture, there exist societal practices institutionalising negative discrimination concerning women, often codified in laws that prohibit women from participating in much of public life or fully competing in the labour market. This zone is characterised by the low status of women in general, high fertility rates coupled with low age at first marriage, high maternal and infant mortality rates, higher rates of female illiteracy, lower levels of female educational enrolment, low female labour force participation, and the lack of women's political participation and political rights (Moghadam, 2003;Caldwell, 1982Caldwell, , 2004Littrell & Bertsch, 2013;Afiouni et al, 2019).…”
Section: Institutional Factorsmentioning
confidence: 99%